Strength and compressibility of soft soil reinforced with bottom ash columns - Muzamir, Hasan (2013)
Stone column could be used as a ground improvement technique where a portion of the soft soil is replaced with granular material such as crushed rocks or sand which is proven to increase bearing capacity and accelerate the dissipation of excess pore water pressure. This research was aimed to investigate the role of bottom ash columns in improving the shear strength and compressibility of soft reconstituted kaolin clay. This was done by determining the effects of area replacement ratio, height penetrating ratio and volume replacement ratio of a single and a group of bottom ash columns on the strength characteristics and also the effects of confining pressure on the compressibility characteristics of kaolin clay reinforced with bottom ash column(s). Among the objectives of this research include establishing a design chart that correlating the undrained shear strength of bottom ash column(s) reinforced kaolin clay with the volume replacement ratio and the mean normal effective stress, through critical state soil mechanics framework. The reinforced kaolin samples were subjected to using Unconfined Compression Test (UCT) and Consolidated Undrained (CU) Triaxial Test. Research variables include diameter and height of the bottom ash columns and effective confining pressure, 0"3 (also equals to mean normal effective stress, p' 0 ) . Analysis of the results had been carried out using the Mohr-Coulomb and critical state failure criteria. Based the results of UCT, it can be concluded that the undrained shear strength generally increased with the increased in the height penetrating ratio but decreased after reaching an optimum improvement at 80 % of height penetrating ratio. The increment of undrained shear strength was also dependent on the area replacement ratio. Without confining pressure, the higher the area replacement ratio, the higher the strength occurred. However, excessive area of replacement decreased the shear strength of the sample reinforced by group columns since the remaining width of the soil sample was too thin to hold the columns. Based on the Mohr-Coulomb failure criteria of the CU test results, the installation of bottom ash columns did not show any significant difference in the effective friction angle. However, it did result in an increase in the apparent cohesion and undrained shear strength of the kaolin clay. It is also proven that the dissipation of pore water pressure was accelerated with the presence of bottom ash columns. Analysis through the critical state soil mechanics framework revealed critical state parameters of M, r and /..., for each samples. Most of the M values for the soil-bottom ash composite lie between 1.25 and 1.33, giving a variation on the friction angle at critical state between 31° to 33°, hence fall under the "mixtures of gravel and sand with fine-grained soils" category. Generally it can be concluded that the shear strength and compressibility of soft clay could be improved by the installation of bottom ash columns. Hence, a design chart was established intended to become a design tool, particularly in the determining the volume of bottom ash needed to form the vertical columns achieve to the required shear strength of the improved clay soil.